Cyclic nigerosyl-1, 6-nigerose-based nanosponges: An innovative pH and time-controlled nanocarrier for improving cancer treatment. (15th August 2018) - Caldera, F.; Argenziano, M.; Trotta, F.; Dianzani, C.; Gigliotti, L.; Tannous, M.; Pastero, L.; Aquilano, D.; Nishimoto, T.; Higashiyama, T.; Cavalli, R.
Highlights: New tetraglucose-based biomaterial, comprising cyclic nigerosyl-1-6-nigerose (CNN). Cross-linked nanoparticles, named CNN-nanosponges, for doxorubicin delivery. pH-dependent and prolonged release kinetics of doxorubicin from CNN-nanosponges. In vitro enhanced anticancer activity of doxorubicin-loaded nanosponges. Abstract: The design and structural optimisation of a novel polysaccharide-based nanomaterial for the controlled and sustained release of doxorubicin are here reported. A cross-linked polymer was obtained by reacting a tetraglucose, named cyclic nigerosyl-1-6-nigerose (CNN), with pyromellitic dianhydride. The cross-linking reaction formed solid nanoparticles, named nanosponges, able to swell as a function of the pH. Nanoparticle sizes were reduced using High Pressure Homogenization, to obtain uniform nanosuspensions. Doxorubicin was incorporated into the CNN-nanosponges in a good extent. DSC and solid state NMR analyses proved the drug interaction with the polymer matrix. In vitro studies demonstrated pH-dependent slow and prolonged release kinetics of the drug from the nanoformulation. Doxorubicin-loaded CNN-nanosponges were easily internalized in A2780 cell line. They might considered an intracellular doxorubicin reservoir, able to slowly release the drug over time. CNN-nanosponges may be promising biocompatible nanocarriers for the sustained delivery of doxorubicin with potential localised application in cancer treatments.